Oral corticosteroids and asthma in children: Practical considerations. (3rd February 2020) - De Filippo, Maria; Clark, Evangéline; Fillard, Anouchka; Diaferio, Lucia; Caimmi, Davide
Abstract: Corticosteroids (CS) are among the most prescribed drugs in pediatrics. In allergy, CS are prescribed for several different conditions. If CS show clear benefits when adequately prescribed, CS are also associated with several side effects, well known by pediatricians. As for asthma exacerbations, the oral route is always the preferred one in pediatrics. Several authors debated if the use of a single dose of dexamethasone is better in terms of efficacy, compared with a 3‐ to 5‐day course of prednisone or prednisolone. Another interesting issue that has not been fully clarified concerns whether oral corticosteroids should be prescribed in preschoolers presenting with acute wheezing. The present review aims to review the most recent publications on this topic and to try to clarify which may be the best option in children suffering from asthma exacerbations.